HEAT TRANSFER THROUGH VERTICAL CYLINDER IN STATIONARY FLUID - Arshad, M.; Inayat, M. H.; Chughtai, I. R. (The Nucleus, 2020)
Natural convection heat transfer has been experimentally investigated for high Raleigh number by placing the cylindrical heating element in stationary water. The uniform heat flux has been applied to large L/D ratio in this experiment. The thermal behavior of this heating element has been found in good agreement with the existing information. The temperature distribution along the surface of heating element with respect to the time was recorded. The experimental result showed that the surface temperature of the water in narrow annular space heat sink increases more than that in wide annular space heat sink with respect to time. The heat transfer coefficient, Nusselt number and Raleigh number have been presented for experimental data and the corresponding relation is developed.